(untitled) (Jurnal Ecosolum, 2024)
Variability of soil types in the Quaternary geological formations on the islands presents different soil morphological characteristics. The process of geomorphogenesis and geology determines the characteristics of soil morphology. This study aims to determine the characteristics of soil morphology, pedogenesis process, soil development based on landforms in Quaternary geological formations in North Maluku Islands region. Six soil profiles were observed, which were determined based on geographical location. Descriptive research methods based on USDA standards were used as the basis for determining soil morphological characteristics. The results showed that the pedogenesis process on Quaternary volcanic landforms were caused by a period of volcanic eruptions characterized by thick soils (>100 cm), fairly steep slopes (15 - 25%), no rock outcrops, and an eluviation-illuviation process on the soil profile. While the pedogenesis process on alluvial landforms tends to produce in-situ rock weathering characterized by slow horizon formation and produces a relatively shallow soil solum (<100 cm). The data obtained provide information on soil resources and the research results can also be used as a formulation in conservation efforts on the islands.